Pemberdayaan Karang Taruna: Budidaya Ikan Lele Cegah Putus Sekolah di Desa Sidomulyo - Wawan Sadtyo Nugroho; Nurifky Muhammad Affan; Pipit Puji Lestari; Muhammad Arifin; Nurwidya Restiyono (AJAD : Jurnal Pengabdian kepada Masyarakat, 2023)
Jetis Hamlet is part of Sidomulyo Village in Secang District, Magelang Regency. In this hamlet, many school-aged children are involved in agricultural and construction work. Previously, the Karang Taruna youth organization in Jetis Hamlet had started a catfish farming business. However, in the last two years, this business has experienced problems due to fish disease. The purpose of this activity is to motivate partners to increase their understanding of catfish farming, increase awareness of the problem of school dropouts, and reduce poverty levels. The results of this activity show that the establishment of this empowerment program has succeeded in overcoming problems in the catfish farming group. Through consistent guidance at various stages of the project and support for start-ups, the program has been successful in restoring and growing catfish farming businesses collectively.